SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN DARI EKSTRAK ETANOL BUAH TERONG UNGU (Solanum melongena L.) - Ni Wayan, Martiningsih; I Nyoman, Sukarta; Putu, Eppy Yuniana (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 2 Juli 2014, 2014)
Phytochemical screening and antioxidant activity test of the ethanol extract of eggplant fruit (Solanum melongena L) have been done. Extraction is done by maceration method using ethanol. Phytochemical screening is done by testing the qualitative class of antioxidant compounds such as alkaloids, flavonoids, tannins, saponins, glycosides, anthraquinone, and steroids / triterpenoids. Phytochemical screening results indicate the presence of alkaloids and flavonoids. Test of the antioxidant activity of the ethanol extract of eggplant fruit with DPPH method using UV-Vis spectrophotometer resulted the DPPH antioxidant activity optimum in 29 th minute and the 58 th minute with a maximum wavelength of DPPH solution of 513 nm. Testing the power of antioxidants compared to ascorbic acid as a positive control showed by IC 50 of 535.89 ppm in 29 th minute and 385.06 ppm in 58 th minute.
Keywords: eggplant fruit (Solanum melongena L), antioxidant, phytochemical screening, DPPH, ascorbic acid, UV-Vis spectrophotometer